A study on training frontline health workers for prevention, early recognition and treatment or transfer of women with post-partum haemorrhage using mamanatalie - Vadvadgi, Nikhita B.; Shailaja, Nageshu; Krishna, Lingegowda; Krishna, Kirtan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of the present study was to train frontline health workers (FHW) on prevention, early recognition and treatment/transfer of women with post-partum haemorrhage using mamanatalie and to compare their pre-training and post training knowledge and skills, and to reassess the knowledge and skills of the trainees after six months. Methods: Training of 159 FHW belonging to the nine Primary Health Centres (PHC) of Kuppam constituency was conducted using mamanatalie. Pre and post training knowledge and skill assessment were compared using questionnaires and the mamanatalie. Reassessment of knowledge and skill was done after six months. Results: Among 159 participants 93% scored more, 3% scored same and 4% scored lesser in post training when compared to pre-training test. In the follow up knowledge assessment after six months 73 trainees were lost for follow up, among the remaining, 8% scored more, 16% scored same and 76% scored less when compared to the post training test. However, the follow up scores were higher than the pre-training scores. In the skill test, 82% scored more than 80%. Four trainees were lost for follow up skill assessment, among the remaining, 16% scored more, 23% scored same and 61% scored less when compared to the initial skill test scores Conclusions: The training increased knowledge, skill and confidence among the trainees. It has the potential to lead to improved clinical outcomes, especially in the rural areas. Revision sessions may help in better retention of knowledge and skill.